The Influence of Employee Competence, Work Motivation, and On The Job Training on Employee Performance In The Digital Creative Industry (Study on The Podcast Somestory Jakarta) - Havelyne Octaviana Damaling; Acep Samsudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the creative industry in the digital era encourages media companies to have human resource capable of delivering optimal performance in a dynamic and competitive work environment. Podcast Somestory, as a media company engaged in podcast and TikTok content production, requires employees who possess competence, work motivation, and adequate job training to support the achievement of organizational goals. This study aims to analyze the effect of employee competence, work motivation, and on the job training on employee performance at Podcast Somestory. This study employed a quantitative approach with data collected through questionnaires distributed to 78 respondents using a saturated sampling technique. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 31. The results showed partially, employee competence had a positive and significant effect on employee performance with a significance value of <0,001. Meanwhile, work motivation and on the job training did not have a significant effect on employee performance, with significance values of 0,674 and 0,554, respectively. However, simultaneously, employee competence, work motivation, and on the job training had a significant effect on employee performance. These findings indicate that employee competence is the most dominant factor in improving employee performance in the creative industry, particularly at Podcast Somestory .